2020
DOI: 10.1016/j.ejphar.2020.173594
|View full text |Cite
|
Sign up to set email alerts
|

Integrative transcriptomics analysis of lung epithelial cells and identification of repurposable drug candidates for COVID-19

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease, more commonly COVID-19 has emerged as a world health pandemic. There are couples of treatment methods for COVID-19, however, well-established drugs and vaccines are urgently needed to treat the COVID-19. The new drug discovery is a tremendous challenge; repurposing of existing drugs could shorten the time and expense compared with de novo drug development. In this study, we aimed to decode molecular signatures and path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 65 publications
10
48
1
Order By: Relevance
“…S2 D). As expected, immune related pathways like interleukin signaling have also been reported by others following analysis of SARS-CoV-2 infection datasets 18 , 19 . Our workflow (modified) has also provided in silico confirmation of the anti-inflammatory and pro-immune effects of oxytocin 70 and the antidepressant fluoxetine 71 , which is also currently in trial for the treatment of COVID-19 (NCT04377308, and others).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…S2 D). As expected, immune related pathways like interleukin signaling have also been reported by others following analysis of SARS-CoV-2 infection datasets 18 , 19 . Our workflow (modified) has also provided in silico confirmation of the anti-inflammatory and pro-immune effects of oxytocin 70 and the antidepressant fluoxetine 71 , which is also currently in trial for the treatment of COVID-19 (NCT04377308, and others).…”
Section: Resultssupporting
confidence: 83%
“…Integrating the results of SARS-CoV-2 transcriptomic analyses generated in infected cell lines, human tissues and even organoids 16 with computational approaches has proven especially fruitful. Such studies identified FDA-approved antivirals 17 and a broad range of kinase inhibitors as potential candidate treatments for COVID-19 18 20 . Importantly, transcriptional analyses have provided additional support for the use of drugs like dexamethasone 17 and chlorpromazine 19 that are already undergoing clinical trial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chronic inflammation has been recognized as a causative factor for the progression of cancer [ 45 ]. Immune systems, cytokines overproduction and cytokine-mediated signaling provided key features in lung inflammation in response to COVID-19 infections [ 46 ], which are consistent with our findings. This study identified wnt signaling pathways, IL-17 signaling pathway, TNF signaling pathways as key signaling pathways associated with COVID-19 and cancers which is consistent with previous reports that identified these altered pathways in COVID-19 [ 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…Immune systems, cytokines overproduction and cytokine-mediated signaling provided key features in lung inflammation in response to COVID-19 infections [ 46 ], which are consistent with our findings. This study identified wnt signaling pathways, IL-17 signaling pathway, TNF signaling pathways as key signaling pathways associated with COVID-19 and cancers which is consistent with previous reports that identified these altered pathways in COVID-19 [ 46 ]. Specifically, the “cytokine storm” seen in COVID-19 patients is the result of severe immune response by the host that deteriorate the conditions of the patients [ 46 ].…”
Section: Discussionsupporting
confidence: 91%